If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 + -5X = 97 + -6X Solving 64 + -5X = 97 + -6X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6X' to each side of the equation. 64 + -5X + 6X = 97 + -6X + 6X Combine like terms: -5X + 6X = 1X 64 + 1X = 97 + -6X + 6X Combine like terms: -6X + 6X = 0 64 + 1X = 97 + 0 64 + 1X = 97 Add '-64' to each side of the equation. 64 + -64 + 1X = 97 + -64 Combine like terms: 64 + -64 = 0 0 + 1X = 97 + -64 1X = 97 + -64 Combine like terms: 97 + -64 = 33 1X = 33 Divide each side by '1'. X = 33 Simplifying X = 33
| 4z+-9z+6=-4 | | 3(w-3)+6=0 | | X+9=14+11 | | 11=-9a+4a | | 3b^2=0 | | N/3=15/5 | | 7X+95=161+6X | | (1/2)(4/19)=x | | 2n+(-9)=53 | | 1/4x+5=-1 | | 5(x-3)-2(x+1)=15 | | 11=-11x+5x | | 3=4(x-2)-x | | k^2+3k-108=0 | | (4z+2)+(69-4z+19)=90 | | 2n+(-9)= | | 7x^2+43x+40=0 | | (4/20)(6/20)=g | | x=z*z+4y | | 14/15+3/5= | | 3X-54=2X-32 | | 3x-5=20-2x | | 23x=2x+7 | | 9x+1/4=5/8 | | -7y-40=y | | (7/28)(6/27)=g | | 4a+6a+2a= | | (4z+2)+(69-4z+y+19)=90 | | z+13/4=x | | 4x^2+5x=-10 | | 238.64=3.14D | | X^2-30x+135=0 |